Biokonversi Pelepah Daun Nipah Menggunakan Jamur Tiram Putih Ditinjau Dari Komposisi Kimia dan Kecernaan Serat - Suryadi Suryadi; Hardi Syafria (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The study aims to determine the chemical composition and digestibility of midrib palm leaves from bioconversion results. Solid bioconversion using white oyster mushroom inoculum as a starter. This study used a completely randomized design (RAL) with 6 treatments and 3 replications. As a treatment  the white oyster mushroom inoculum consisted of 6 levels, namely 0g (with inoculum), 5g, 10g, 15g, 20g and 25g kg-1 substrate. The variables measured are the chemical composition and digestibility of nipah leaf midrib fiber bioconversion products. The results showed that organic matter content, ADF digestibility and nipah leaf midrib cellulosa bioconversion results were significantly different (P<0.05) but the dry matter content, crude protein and NDF digestibility did not show significant differences (P>0.05) due to the levels of white oyster mushroom inoculum. The best digestibility occurred at the levels of white oyster mushroom inoculum 20g kg-1 substrate with acid digestibility fiber 27,31% and cellulose 31,08%. It can be concluded thah the level of white oyster mushroom inoculum 20g kg-1 substrate for nipah leaf midrib bioconversion results is the best.